2017
DOI: 10.1128/jvi.00423-17
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of RNA 5′-Terminal Deletions on Coxsackievirus B3 RNA Replication and Ribonucleoprotein Complex Formation

Abstract: Group B coxsackieviruses are responsible for chronic cardiac infections. However, the molecular mechanisms by which the virus can persist in the human heart long after the signs of acute myocarditis have abated are still not completely understood. Recently, coxsackievirus B3 strains with 5=-terminal deletions in genomic RNAs were isolated from a patient suffering from idiopathic dilated cardiomyopathy, suggesting that such mutant viruses may be the forms responsible for persistent infection. These deletions la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 77 publications
(74 reference statements)
2
56
0
Order By: Relevance
“…Interestingly, a series of recent studies has shown that persistent coxsackievirus genomes mutate, undergoing 5=-terminal deletions (ϳ7 to 49 nucleotides [nt]) that are associated with long-term viral persistence (43, 45-48). Notably, the 5=-terminally deleted picornavirus genomes have been shown to be capable of replicating, resulting in low-yield infectious virus production (48,49). Collectively, these observations suggest at least two potential mechanisms for picornavirus genome persistence: (i) continuous low-level replication in persistently infected cells and/or (ii) cycles of productive and nonproductive infection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, a series of recent studies has shown that persistent coxsackievirus genomes mutate, undergoing 5=-terminal deletions (ϳ7 to 49 nucleotides [nt]) that are associated with long-term viral persistence (43, 45-48). Notably, the 5=-terminally deleted picornavirus genomes have been shown to be capable of replicating, resulting in low-yield infectious virus production (48,49). Collectively, these observations suggest at least two potential mechanisms for picornavirus genome persistence: (i) continuous low-level replication in persistently infected cells and/or (ii) cycles of productive and nonproductive infection.…”
Section: Discussionmentioning
confidence: 97%
“…Swabs (oral, nasal, and rectal/fecal) and blood samples (serum and whole heparinized blood) were collected during the acute phase (days 0, 1, 3, 5, 7, 14, 21, 28, and 35 p.i.) and chronic/persistent phase (days 46,47,48,49,50,51,52,53,54,55,56,57,58,59, and 60 p.i.) of the experiment.…”
Section: Fig 10mentioning
confidence: 99%
“…This oriL-3CD interaction involves the hairpin domain d of oriL and the 3C pro moiety of 3CD, as originally demonstrated by Andino et al (90,94). The interaction between these ligands is important for the initiation of the synthesis of both the viral (positive) and complementary (negative) RNA strands (89,93,(95)(96)(97)(98). It was recently shown that (at least in the case of coxsackievirus B3 [CVB3]) oriL, which is required for efficient genome replication, is not indispensable for viral viability: its removal does not kill the virus but rather decreases the efficiency of its RNA replication ϳ10 5 -fold (99).…”
Section: Introductionmentioning
confidence: 83%
“…2A). This element plays multiple roles in viral reproduction, mainly through promoting formation of a complex ribonucleoprotein (RNP) structure involving several viral and host proteins (89)(90)(91)(92)(93). An essential component of this complex is the viral RdRP (3D pol ), which is recruited there in the form of its precursor, 3CD, i.e., covalently linked to the viral protease (3C pro ) (91).…”
Section: Introductionmentioning
confidence: 99%
“…That these deletions would impede viral RNA replication is consonant with the fact that the first ~100 bases of the 5′ noncoding region of CVB3 (and other enteroviruses) are folded into a structure that visually resembles a clover leaf, and plays a vital role in the syntheses of both positive and negative strands. Some time ago, our laboratory reported that deletion of as few as 32 bases at the 5′ end of the CVB3 cloverleaf had a profound negative impact on CVB3 replication, but had minimal impact on the molecule’s suitability as a template for translation (Hunziker et al, 2007), and more recent studies have shown that TD virus replication is ~10 5 -fold less robust than that of the wt virus (Jaramillo et al, 2016; Leveque et al, 2017; Smithee et al, 2015). TD CVBs also have been identified in humans.…”
Section: Introductionmentioning
confidence: 99%